Assessment of academic difficulties in culturally and linguistically diverse school students. Issue 1 (3rd March 2020) - Velasco Leon, Azucena; Campbell, Marilyn
Abstract: The increasing tendency of immigration and forced migration practices around the world has made countries' populations culturally and linguistically diverse. Australia is considered one of the most culturally diverse countries in the world. Consequently, the proportion of school-aged children with different culture and language is also increasing. Thus, school psychologists and guidance counsellors face the challenge of designing fair assessment practices and sound interventions for culturally and linguistically diverse (CALD) students who experience difficulties with their learning. Although many multicultural countries have extensive research regarding the assessment of learning difficulties in CALD students, Australia lacks this research. This study explored the most common assessment strategies that school psychologists and guidance counsellors usually implement in their assessment of CALD students. These results were then compared to a best practice model from the literature. In order to understand the current practices of school psychologists and counsellors in Australia who have assessed CALD children, a survey was administered to 34 school psychologists and counsellors. It was found that the reported strategies and protocols were very close to the ones proposed by experts, which was an unexpected outcome of this study. Implications for school psychologists and counsellors are discussed.